The Effect of Health Education on The Motivation of Posternative Women in Exclusive Assessment in The Jatiranggon Puskesmas Area Bekasi City - Azzahroh, Putri; Handayani, Yuyun Ulfa Dwi; siauta, Jenny Anna (Rajaki of Tulip Medika Publisher, 2023)
Background: Breast milk is a good nutritional intake for optimal growth and development in infants and is given from 0–6 months without adding other foods or drinks. In 2017 in Indonesia, the national exclusive breastfeeding coverage, namely 55%, is still far from the target of 80%. Meanwhile, exclusive breastfeeding coverage in Bekasi City was 33.81%. Purpose: This study aims to determine the effect of health education on the motivation of postpartum mothers in giving exclusive breastfeeding at the Jatiranggon Health Center, Bekasi City. Methods: This study used a pre-experimental design one group pretest posttest approach. Samples were collected using quota sampling totaling 30 postpartum mothers who breastfeed in the Jatiranggon Health Center area. The questionnaire has been tested for validity and reliability. Data analysis was performed using the Wilcoxon Signed Rank Test. Result: Before being given health education, 53% of the 30 respondents had moderate motivation in exclusive breastfeeding. After being given health education, there was a significant 90% increase in the respondent's motivation. The Wilcoxon Signed Rank Test shows a value of 0.000, which means that there is a significant effect of health education on the motivation of postpartum mothers in exclusive breastfeeding. Conclusion: Health education is proven to have an effect on increasing the motivation of postpartum mothers in exclusive breastfeeding. It is hoped that postpartum mothers will increase their knowledge about exclusive breastfeeding from various media and attend health education.